Synthesis and Characterization of Chitosan–Silver Nanocomposite Film: Antibacterial and Cytotoxicity Study - Ogungbesan, Shephrah Olubusola (2024)
This study is aimed at the in situ preparation and antibacterial study of silver nanoparticles within the matrix of an eco-friendly, biocompatible, biodegradable, and bioavailable biopolymer (chitosan) to form Chi–AgNP film via multiple noncovalent interactions between the organic polymer and the nanoparticles. The film is fully characterized by infrared and ultraviolet spectroscopy, scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, and thermogravimetric analysis. The characterization confirms the successful incorporation of silver nanoparticles into the polymeric network. Infrared spectroscopy reveals peaks corresponding to the vibration of functional groups present in chitosan with enhanced intensity and blueshifts caused by the presence of silver nanoparticles. Well-monodispersed spherical silver nanoparticles with an average size of 10 nm are observed in the Chi–AgNP film. The surface plasmon resonance at 447 nm is consistent with a typical silver plasmon. Furthermore, the antibacterial effects on E. coli and S. aureus were determined and attributed to the release of AgNPs observed by UV absorption.